Kebiasaan Makan Balita dan Ketahanan Pangan Rumah Tangga di Daerah Kesetaraan Gender Rendah dan Tinggi di Indonesia: Children’s Food Habits and Food Security among Households in Low and High Gender Equality in Indonesia - Ikeu Tanziha; Ali Khomsan; Titik Sumarti; Resa Ana Dina; Rian Diana; Yeni Rohmaeni (Amerta Nutrition, 2023)
Backgrounds: More women experience gender inequality even though they play a significant role in household food security. Women have more limited access to education and employment opportunities, thus affecting economic autonomy and lower bargaining power within the household. Gender inequality experienced by women has an impact on household food insecurity. Objectives: To analyze differences in the eating habits of families and children under five and household food security among households with high and low gender equality. Methods: This cross-sectional study was conducted in areas of low and high gender inequality in Indonesia. A total of 303 households with children under five participated in this study. Data collection included family characteristics, Household Food Insecurity Access Scale (HFIAS), and families and children's eating habits. The Mann-Whitney difference test examined the differences between variables in two areas. Results: Food insecurity prevalence in low gender equality areas (moderately food insecure 45.6%, severe 23.8%), significant differences (p<0.05) within high gender equality areas (moderately food insecure 34.6%, severe 17.3%). Families in areas of high gender equality, more frequently eating three meals a day (p<0.001), eating together (p=0.003), husbands (p<0.001), and children (p<0.001), have a higher role as menu deciders. There were significant differences (p<0.05) in the eating habits of children under five in the two areas. Conclusions: Households in low gender equality areas are more food insecure and have low-income family eating habits than high gender equality areas. Therefore, special attention is needed from the government to improve gender equality through increased education and women's economic empowerment.